Disaster Mitigation for Palu City Residents in Dealing with Liquefaction Disasters in Accordance of Spatial Patterns of Palu City, Central Sulawesi Province, Indonesia. - Yudi Kuswandi; Jossi Erwindi; Moh. Sapari Dwi Hadian; Dicky Muslim (UIR PRESS, 2020)
Potential natural hazards in Palu City by paying attention to the real physical characteristics of Palu City are categorized as having a high level of disaster hazard. The geological character of both the geological structure and geological engineering in the Palu region shows the great potential for geological disaster hazards. On September 28, 2018, at 18: 02 CIT, an earthquake measuring 7.4 on the Richter scale, the quake's center located in 26 km of Donggala district and 80 km northwest of Palu City. By observing the epicenter's location and the depth of the hypo-central earthquake, it appears that this shallow earthquake occurred due to activity in the Palu Koro fault zone. This fault is the most active in Sulawesi and is the most active in Indonesia with a movement of 7 cm per year. Liquidity disasters or ground liquefaction are also the effects of an earthquake. Shocks a massive quake causes the soil to melt this thing occurs when the saturated soil loses strength and stiffness due to stress. The Petobo area and the Balaroa - Perumnas are close to the Palu Koro active fault line and the land in the area is composed of soft material from the sedimentation process. This area is shallow groundwater with high soil permeability values, namely in the Petobo area and Perumnas - Balaroa. The purpose of this study is to analyze the potential liquefaction disaster in Palu City and analyze the Palu City resident ability against Liquefaction Hazard Prone. This research uses a descriptive qualitative analysis method. Potential liquefaction disasters were analyzing qualitatively based on geological conditions and disaster locations. Disaster mitigation capabilities were analyzed qualitatively based on the Palu City Spatial Pattern. One of the hazards caused by an earthquake that has the potential to be a disaster in Palu City is liquefaction. The ability of residents to mitigate liquefaction in Palu City is influenced by local wisdom which is reflected in ancient times when people lived in the highlands or hills. the concept of building structures, land use, and spatial planning patterns in Palu City which can reduce the threat of liquefaction.